Transcriptomic analysis of leukocyte immunometabolic dynamics in hemorrhagic sepsis in Piaractus mesopotamicus - Claudiano, Gustavo S. [UNESP]; Sampaio, Larissa A. F.; Andrade, Sónia C. S.; Souza, Elaine C.; Yunis-Aguinaga, Jefferson; Marcusso, Paulo F. [UNESP]; Ferreira, Juliana N.; Leão, Andrya L.; dos Santos, Thayná M.; Pereira, Layana A. B.; dos Santos, Laine P. C.; Coutinho, Luiz L.; et al. (Springer Nature, 2025)
Sepsis caused by Aeromonas hydrophila in Piaractus mesopotamicus triggers a complex transcriptomic reprogramming in circulating leukocytes. This study employed RNA-Seq to profile temporal changes in gene expression during the early stages of sepsis (1, 3, 6, and 9 h post-infection, HPI). A total of 17,698 differentially expressed genes (DEGs) were identified, with transcriptional peaks at 3 and 9 HPI. Functional classification (KOG) revealed enrichment in genes related to energy metabolism, amino acid metabolism, and protein synthesis. Gene Ontology (GO) and KEGG pathway analyses showed that leukocytes preferentially activated pathways involved in anaerobic glycolysis, the Krebs cycle, and lipid metabolism—particularly steroid hormone biosynthesis. Key immunometabolic pathways, including PI3K-AKT, mTOR, and TLR signaling, were dynamically modulated, indicating their role in maintaining ionic balance and promoting leukocyte survival during systemic inflammation. In addition, substantial reprogramming of iron and calcium metabolism was observed, suggesting a host strategy to limit bacterial growth by restricting access to essential micronutrients. These metabolic shifts correlated with disease severity, as evidenced by the high mortality rate (71.4% at 120 HPI) and pronounced histopathological damage in vital organs. Altogether, these findings demonstrate that leukocytes initiate a robust but potentially deleterious immunometabolic response to A. hydrophila, contributing both to host defense and to tissue injury. This work provides valuable molecular insights into the pathogenesis of septicemia in fish and offers a foundation for developing targeted strategies to mitigate Aeromonosis in aquaculture.